Distorted trade barriers - Matthew T. Cole (University College Dublin, UCD School of Economics, 2011)
Since firm heterogeneity has been introduced into international trade models, the importance of firm entry and exit (the extensive margin) has been highlighted. In fact, Chaney (2008) illustrates how accounting for this extensive margin and heterogenous firms alters the standard gravity equation; thereby reversing the previously predicted effect the elasticity of substitution has on the elasticity of trade flows. Furthermore, Cole (forthcoming) points out that ad valorem tariffs affect the extensive margin quite differently than the commonly used iceberg transport cost. In this paper, I show that the elasticity of trade flows with respect to tariffs is more elastic than that of iceberg transport costs. Thus, elasticity estimates derived from variables such as distance may underestimate the effect caused by a change in tariffs.
Keywords: F12; F13; F17; 330; Intra-industry Trade; Gravity; Firm heterogeneity; Monopolistic competition